Kegiatan Edukasi Tahapan Pemberian Makanan Pendamping ASI Sebagai Upaya Penerapan Penyuluhan Kesehatan Rumah Sakit di Luar Gedung - Prasetyorini, Anif; Ramhawati, Indri; Shandy, Rafifah Nur; Ananta, Novian Saga; Cahyaningrum, Rina; Nafa R, Tria; Rahmawati, Indah (Jurnal Abdimas Jatibara, 2024)
Indonesian Nutritional Status Survey (SSGI), the prevalence of stunting has increased, partly due to less than optimal visits by toddlers to posyandu for measurements and weighing. Empowerment is the initial milestone in Hospital Health Promotion activities which can be implemented outside the building. The objectives to empower through education about the stages of giving complemengtary breast milk to mothers of toddlers. The Methods: outreach to the community around the hospital by providing pre-tests and post-tests to measure knowledge. The Results  showed two approaches were used to carry out the activity: evaluation and presentation. The presentation and question-and-answer period is the first step. Four activities make up the presentation: the opening, introduction, implementation, and conclusion. The aim and objectives of the exercise are explained as part of the introductory activity. The explanation of the planned activities completes the introductory phase. Implementation efforts include giving participants information on what is meant by "complementary foods for breast milk," the advantages of MP ASI, the different kinds of main foods, and the different kinds of snacks. explanations of age groups, child growth, MP ASI texture, MP ASI frequency, and MP ASI amount per portion, as well as things to consider when using or preparing food. The danger of giving MP ASI if is not age approriate. The second stage is the evaluation stage which shows that there is an increase in the knowledge of stage of giving MP ASI , the participant quota is fulfilled and the material is delivered to the participants. There needs to be re-empowerment of mothers of toddlers.